Role of Delnido Cardioplegia in Reduction of Post Cardiac Surgery Ventricular Arrythmias - Abida Iqbal, Salman Ahmed, Afzal Qasim, Masroor Hussain Sharfi, Erum Shahzadi Malik, Muhammad Hamza Muhammad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To investigate the association of Delnido’s Cardioplegia (DNC) as a prophylactic treatment for ventricular arrhythmias associated with cardiovascular surgery in adults. Methodology: This observational prospective study was conducted at NICVD, Larkana, Pakistan from December 2022 to May 2023. Study was started after approval from hospital ethical committee. Baseline variables were age, medical history, APACHE II score, and left ventricular ejection fraction (EF). Intraoperative data, such as surgery type, operation duration, CBP time, aortic occlusion time (AB), and cardioplegia type, were also collected. Patients were grouped by cardioplegia type. Postoperative data included maximum serum potassium, cardiac enzymes (CK, CK-MB) within 24 hours, EF within 48 hours, incidence of VA, and ICU stay length. Results: The incidence of post-ventricular arrhythmia was comparable between the groups, with 11 cases 18.3% in the DNC group and 12 cases 20% in the STH group (p=1.000). Notably, the ICU stay was shorter in the DNC group 3.50±0.51 days compared to the STH group 4.47±0.50 days (p<0.001). Conclusion: Del Nidocardioplegia reduces postoperative ventricular arrhythmias and preserves myocardial stability. It provides prolonged cardiac arrest with a single dose, shortening bypass time and reducing ICU stay in complex cardiac surgeries. Keywords: Delnidocardioplegia, Ventricular arrhythmias, Cardiac Surgery, Hospital stay, Ejection fraction